A Study on Thermal Insulation of Cement Bricks Incorporate with Cellulose Fiber - Kamaruzzaman, Ahmad Syamir; Wan Jusoh, Ts. Dr. Wan Amizah (Progress in Engineering Application and Technology, 2023)
Cement brick is one of the important and common building materials that widely being used in the construction industry. Common brick that being using in the construction industry nowadays are poor in thermal insulation. The objective of this study is to study the physical properties of cellulose fiber as added material in cement bricks. Next, this study is to determine the mechanical properties of cement bricks containing cellulose fiber. Lastly to evaluate the thermal performance for cement brick containing cellulose fiber compare with conventional cement bricks. The materials that being used is the cellulose fiber powder made from the bamboo plant with different percentage that added into the mixture of cement bricks. The test that has being carried out for this study is the density test, water absorption test, ultrasonic pulse velocity test, compressive strength test and thermal conductivity test. From this study, it can be observed that the value of the thermal conductivity of the bricks for the specimens sample of 10% obtained the lower value of thermal conductivity with 0.153 W/mᵒC for the age of 7 days of curing and 0.161 W/mᵒC for the age of 28 days of curing and the density is 2335.71 kg/m3 for 7 days and 2345.24 kg/m3 for 28 days with the compressive strength of 33.18 kN/m2 and 41.04 kN/m2 for 7 days and 28 days. From the result that has obtained, the value of thermal conductivity of all specimens has meet the standard requirements for thermal conductivity which is 0.69 W/mᵒC and below. The good production of bricks should obtain low thermal conductivity so that the buildings that use the bricks is cool in summer especially in the hot weather in Malaysia.